Awareness and Availability of Instructional Media for Learning Mathematics by Public Secondary School Students in Benin Metropolis: Counselling Implication - Ikuereye, Evbakoe Pedro; Igbineweka, Martins Noyosase (NIU Journal of Social Sciences; Vol 6 No 2 (2020): KIU Journal of Social Sciences, Vol. 6 No. 2, June 2020, 2020)
This paper assessed the awareness and availability of instructional media for learning Mathematics by public secondary school students in Benin metropolis . Students in junior secondary schools from the three local government areas in the metropolis formed the population for the study. Three schools were randomly selected from each local government respectively, with fifty (50) students from each schools and this made up the sample for the study. A questionnaire titled Awareness of instructional media for learning Mathematics which was subjected to Cronbach alpha statistics with a reliability coefficient of 0.78 and a checklist titled: Availability of instructional media for Mathematics students were the instruments for the collection of data. The data collected were analysed using frequency count, mean, standard deviation and t-test. That, Mathematics students in the metropolis be enlightened on the instructional media that can aid their learning of Mathematics and parents/guardians should be encouraged to provide some basic instructional media were some of the recommendations. Keywords: Awareness, Availability, Instructional Media, Mathematics, Benin Metropolis and Counselling Implication.